Influencing Factors to Perception of Death in the Elderly - M. Sajidin (Kirana Publisher (KNPub), 2023)
The elderly represent the end of the human life cycle. The physical and psychological state of the elderly will alter at this time. The elderly sometimes believe that death will strike at any moment when circumstances are unfavorable. Even if this awareness of the look of death appears, each person's or group's perception or understanding of death may differ. The purpose of this study is to ascertain how elderly people see death. Methods: This study employed the phenomenological design for qualitative research literature review approach, which is derived from three databases (PubMed, Scient Direct, and Google Sholar) for prior investigations. The papers were published between 2016 and 2020. Results and analysis: One international journal and three national periodicals were the primary sources for this study. Discussion and Conclusion: According to research findings based on multiple journals, elderly people have a very diverse understanding of death. However, it is clear that elderly people view death as an inevitable event that cannot be rejected or avoided, so they are aware that it may happen at any time. For the elderly, better oneself and growing closer to God is also a form of self-evaluation. Every person has a different perspective on mortality in the elderly. Spiritual considerations, familial support factors, and experience factors are all elements that have an impact on how older people perceive death. The experience factor is the end consequence of the major component influencing perception of death.